Combinational effect of NiFeOx/Tb(OH)x as hole extractor for enhanced charges separation and stability of BiVO4 photoanode for solar water splitting - Yuxuan Chen; Jiayi Huang; Jingyu Zhou; Xiang Li; Hao Yang; Yongchao Huang (Materials Today Advances)
Development of efficient and stable photoanodes for the efficient oxygen evolution reaction highly needs for photoelectrochemical (PEC) water splitting. Herein, we demonstrate terbium hydroxide (Tb(OH)x) for significantly boosting the oxygen evolution activity and stability of NiFeOx/BiVO4 photoanodes. The Tb(OH)x nanoparticles in NiFeOx/Tb(OH)x/BiVO4 photoanode as hole extractor rapidly transfer holes from BiVO4 to NiFeOx, effectively improving the bulk charge separation efficiency and water oxidation kinetic efficiency, thus improving the PEC performance. The resulting NiFeOx/Tb(OH)x/BiVO4 photoanode achieves an excellent photocurrent density of 5.75 mA/cm2 and excellent stability with 110 h at a potential 1.23 V versus reversible hydrogen electrode (RHE) under AM 1.5G illuminations. This work not only analyzes the role of Tb(OH)x as a hole extractor in the photoanode, but also provides a promising strategy for designing the efficient PEC photoanodes.